ANALISIS PEMASARAN KACANG TANAH (Arachis hypogaea L.) ASAL DISTRIK KEBAR KABUPATEN TAMBRAUW PROVINSI PAPUA BARAT DAYA - Awabiti, Aplesia I; Amestina Matualage; Martua Hutabarat (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2025)
This research aims to determine the marketing channels and marketing margins, as well as to assess the marketing efficiency of peanuts, originating from the Kebar District of Tambrauw Regency. The data collection method was conducted using simple random sampling and snowball sampling. This study discusses the general background of the respondent farmers in the Kebar District who cultivate peanuts in the villages of Anjai and Jafai, as well as the marketing actors such as Collector Traders, Retail Traders, and Consumers in the Tambrauw Regency Market and the city of Manokwari. Based on the results obtained, there are three marketing channels: the first channel involves farmers selling their peanut production directly to consumers. The second channel involves farmers selling their peanut production to retail traders. The third channel involves farmers selling peanuts to collector traders, who then sell the peanuts to retail traders at the market, and finally, the retail traders sell the peanuts to consumers. In this study, the most efficient marketing channel is channel one, with an efficiency value of 8.67%, and channel one is the channel with the smallest marketing margin, which is zero.